THE TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND EMPLOYEES’ PERFORMANCE: STUDY IN MOTHERS AND CHILDREN HOSPITALS - M Hartadi; V Rudy Handoko; Abdul Muhith; Mamik Mamik (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Purpose – This research aims to test and analyze the influence of transformational leadership style and organizational culture on organizational citizenship behavior (OCB) and employees’ performance in mothers and children hospitals in Indonesia, particularly in East Java Province. Design/Methodology/Approach – The research samples are 89, i.e. 89 nurses and midwives who work in 3 mothers and children hospitals in East Java. The sampling technique uses a population study. The analysis data method used is path analysis. Findings – The research results conclude that: (1) the transformational leadership style significantly influences OCB; (2) the organizational culture significantly influences OCB; (3) the transformational leadership significantly influences employees’ performance; (4) the organizational culture insignificantly influences employees’ performance, and (5) OCB significantly influences nurses’ performance in mothers and child hospitals in East Java. Originality/value – This study is among the few studies that take into account the influence of transformational leadership style and organizational culture on organizational citizenship behavior, particularly within the context of the nurse working in mother and children hospitals.